2022
DOI: 10.1002/hed.27160
|View full text |Cite
|
Sign up to set email alerts
|

Posttreatment FDG‐PET/CT Hopkins criteria predict locoregional recurrence after definitive radiotherapy for oropharyngeal squamous cell carcinoma

Abstract: Background Metabolic response assessment for oropharyngeal squamous cell carcinoma (OPSCC) aids in identifying locoregional persistence/recurrence (LRR). The Hopkins Criteria are a standardized qualitative response assessment system using posttreatment FDG‐PET/CT. Methods We conducted a retrospective cohort study of patients with node‐positive OPSCC treated with definitive (chemo)radiotherapy. We assessed Hopkins Criteria performance for LRR, then developed and validated a competing‐risks model. Results Betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Recently, posttreatment FDG-PET/CT Hopkins criteria showed an accuracy of 85% for predicting locoregional recurrence after definitive radiotherapy for oropharyngeal squamous cell carcinoma. [ 14 ] In our study, HAN-MI-RADS sensitivity was near similar at 3 months, and 1 year with an accuracy of 88.6% up to 2 years. Hopkins score showed no significant time dependency in our study and a better accuracy of 92.9%.…”
Section: Discussionsupporting
confidence: 61%
“…Recently, posttreatment FDG-PET/CT Hopkins criteria showed an accuracy of 85% for predicting locoregional recurrence after definitive radiotherapy for oropharyngeal squamous cell carcinoma. [ 14 ] In our study, HAN-MI-RADS sensitivity was near similar at 3 months, and 1 year with an accuracy of 88.6% up to 2 years. Hopkins score showed no significant time dependency in our study and a better accuracy of 92.9%.…”
Section: Discussionsupporting
confidence: 61%
“…These criteria have an excellent interobserver agreement and a high negative predictive value (reported NPV of up to 95%). A recently published validation study on 259 patients with 18 F-FDG PET following definitive radiotherapy for oropharyngeal squamous cell carcinoma showed that a positive Hopkin’s score was associated with local residual disease/recurrence rate of 45% compared to 5% when negative (Hazard ratio, 12.60; p < 0.001) ( 25 ) and these are also predictive of PFS and OS ( 26 ). Additionally, post-therapy the Hopkins criteria on 18 F-FDG PET may identify clinically unsuspected residual disease in up to 19.5% of patients ( 24 , 27 ).…”
Section: Reporting Schemes and Classificationsmentioning
confidence: 99%
“…Each patient was followed up by repeated clinical examinations, and findings of recurrence of tumor were documented. No uniform definition of recurrence exists [ 17 , 18 , 19 ]. In the present study, we have used 6 months as a cutoff and defined recurrence as follows: Recurrence was divided into residual disease (defined as loco-regional recurrence <6 months post-treatment), loco-regional recurrence (defined as loco-regional recurrence ≥6 months post-treatment), or general failure/distant metastasis (defined as distant metastasis >6 months post-treatment).…”
Section: Methodsmentioning
confidence: 99%